Investigating Teachers’ Perception Regarding Brain-based Teaching Method at College Level - Warsi, Lubna Quddus; Ali, Usama Bin; Usman, Amna (Journal of Development and Social Sciences, 2025)
This study investigates teachers’ perception regarding brain-based teaching method. It also identified the challenges faced by teachers in the way of using brain-based teaching at college level. Traditional lecture-centered approaches, although still widely used, are increasingly seen as insufficient for addressing the varied learning needs of modern students. Integrating brain-based teaching principles can help bridge this gap by fostering more interactive, engaging, and learner-centered classrooms. The study used descriptive quantitative survey design. Sample of the study consisted of 503 teachers from public and private colleges from district Multan. Both descriptive statistics and inferential statistical techniques were applied. Findings show that brain-teaching method improves student learning and understanding. Teachers reported increased students’ motivation and satisfaction with brain-based teaching strategies, which ultimately results in enhanced academic achievement. Colleges should provide supportive structures—such as flexible classroom layouts, teaching aids, and manageable class sizes—to make it easier for teachers to apply brain-based strategies.